Leuprolide Acetate Treatment for Ovarian Cysts in Breast Cancer Patients Under Tamoxifen Therapy - Yılmaz Baran, Şafak; Dogan Durdag, Gulsen; Alemdaroglu, Songul; Aydin, Sirin; Celik, Husnu (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: The aim of this study is to evaluate the outcomes of gonadotropin-releasing hormone agonist treatment for ovarian cysts, which are developed during tamoxifen use due to breast cancer. STUDY DESIGN: This was a retrospective cohort study including the patients who were under tamoxifen treatment due to stage I-III breast cancer and who were administered leuprolide acetate for ovarian cysts with low malignancy risk between 2012-2020. RESULTS: Leuprolide acetate was administered to a total of 16 patients with ovarian cysts. The median age was 39.5 (33-52), the median size of the ovarian cyst was 42.5 (39-79) mm, and the median duration of tamoxifen use was 22 (7-36) months. Leuprolide acetate was administered at doses of 3.75 mg for 1 month at 10 (62.5%) patients, 7.5 mg in two months at 3 (18.75%) patients, and 11.25 mg in three months at 3 (18.75%) patients. Ovarian cysts were regressed after treatment at 13 patients, while 3 patients underwent surgery. CONCLUSION: Leuprolide acetate can be used as an option in the treatment of ovarian cysts that develop in breast cancer patients under tamoxifen therapy. Keywords: Breast neoplasms, Gonadotropin-releasing hormone, Ovary, Ovarian cyst, Tamoxifen